2013
DOI: 10.1111/bdi.12168
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal course of aggression among adults with bipolar disorder

Abstract: Objectives Bipolar disorder (BP) has been associated with increased aggressive behaviors. However, all existing studies are cross-sectional and include forensic or inpatient populations and many do not take into account the effects of comorbid conditions. The goal of this study was to evaluate the longitudinal course of aggression among adult outpatients with BP compared with non-BP patients and healthy controls. Methods Subjects with bipolar I disorder (BP-I)/bipolar II disorder (BP-II) (n = 255), non-BP ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…Previous research documented that persons diagnosed with BD reported significantly more difficulty with anger, verbal aggression, physical aggression, and hostility than did control participants, and that these difficulties were sustained across follow-up (Ballester et al, 2014) and even during a state of remission (Johnson et al, in press). Not all persons with BD have such difficulties, however.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous research documented that persons diagnosed with BD reported significantly more difficulty with anger, verbal aggression, physical aggression, and hostility than did control participants, and that these difficulties were sustained across follow-up (Ballester et al, 2014) and even during a state of remission (Johnson et al, in press). Not all persons with BD have such difficulties, however.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, aggression, as well as subjective experiences of anger, continues to be of concern for some with BD even after remission. Anger and aggression are core predictors of functioning (Ballester et al, 2014), mania (Wright et al, 2008), suicidality (Oquendo et al, 2000), and incarceration (Arseneault et al, 2000;Casiano et al, 2008). As such, there is need for richer models that integrate both clinical and personality predictors to enhance treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite most of psychiatric patients are not violent, some severe mental illness, particularly bipolar disorder, personality disorders and schizophrenia, are associated with an increased risk for aggressive behavior (Ballester et al, 2014;Volavka, 2013). Aggressiveness and social behaviors are known to be modulated by classical neurotransmitters, in particular dopamine and serotonin (Comai et al, 2012a), but also by neuropeptides, such as vasopressin and oxytocin (Albers, 2012;Bosch and Neumann, 2012;Calcagnoli et al, 2013;Neumann and Landgraf, 2012;Veenema and Neumann, 2008).…”
Section: Introductionmentioning
confidence: 99%